Exploring Students’ Entrepreneurial Resilience in Higher Education Level: A Phenomenology Study - Marfu’i, Lucky Nindi Riandika; Hartanti, Jahju; Musdalifah, Ana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The students’ competence at college need to be equipped with entrepreneurial orientation and entrepreneurship education to form a high entrepreneurial resilience. College students usually do not have career orientation yet, which is aimed after graduation. They frequently feel confused about starting entrepreneurship because they lack entrepreneurial insight during college. This paper investigated the phenomenon of entrepreneurial resilience of college students and the evaluation of entrepreneurship course delivery for students at all college departments. The method used was a phenomenology study with students as subjects determined through an incidental sampling technique. The data collection techniques were observation and interview. The research results showed no difference in entrepreneurial resilience between males and females, but social experiment strongly influenced their motivation and interest in entrepreneurship. All subjects felt that discussing problems with friends was essential in entrepreneurship during college. Most subjects stated that they lacked insight related to entrepreneurship at college. The research also found that the students’ entrepreneurial resilience was in the medium category. This research recommends that evaluation is required for developing an entrepreneurship course at college concerning entrepreneurship orientation and entrepreneurial resilience.